The association between serum uric acid to high density lipoprotein-cholesterol ratio and non-alcoholic fatty liver disease: the abund study - Kosekli,Mehmet Ali (2021)
SUMMARY OBJECTIVE: Non-alcoholic fatty liver disease, which is characterized by lipid being deposited into hepatocytes, affects nearly one in three adults globally. Inflammatory markers were suggested to be related with hepatic steatosis. Uric acid to HDL cholesterol ratio is proposed as a novel inflammatory and metabolic marker. We aimed to compare Uric acid to HDL cholesterol ratio levels of patients with Non-alcoholic fatty liver disease to those of healthy controls and find out potential correlations between Uric acid to HDL cholesterol ratio and other inflammatory and metabolic markers of Non-alcoholic fatty liver disease. METHODS: Patients with a diagnosis of Non-alcoholic fatty liver disease who were on clinical follow-up in our institution were enrolled in the study as the Non-alcoholic fatty liver disease group, while healthy volunteers were enrolled as the control group. The Uric acid to HDL cholesterol ratio of the groups was compared and potential correlations were studied between Uric acid to HDL cholesterol ratio and fasting blood glucose, transaminases, serum lipids (triglyceride, LDL-cholesterol), weight, and body mass index. RESULTS: The Uric acid to HDL cholesterol ratio of the Non-alcoholic fatty liver disease (13±5%) group was significantly higher compared to the Uric acid to HDL cholesterol ratio of the control (10±4%) group (p<0.001). Uric acid to HDL cholesterol ratio was significantly and positively correlated with fasting blood glucose, transaminases, triglyceride, body weight, waist circumference, hip circumference, and body mass index. A ROC analysis revealed that a Uric acid to HDL cholesterol ratio level greater than 9.6% has 73% sensitivity and 51% specificity in determining Non-alcoholic fatty liver disease. CONCLUSION: Due to the inexpensive and easy-to-assess nature of Uric acid to HDL cholesterol ratio, we suggest that elevated Uric acid to HDL cholesterol ratio levels be considered a useful tool in diagnosing hepatic steatosis.